Radio observations of candidate magnetic O stars - Schnerr, R.; Rygl, K.; van der Horst, A.; Oosterloo, T.; Miller-Jones, James; Henrichs, H.; Spoelstra, T.; Foley, A. (EDP Sciences, 2007)
Context: Some O stars are suspected to have to have (weak) magnetic fields because of the observed cyclical variability in their UV wind-lines. However, direct detections of these magnetic fields using optical spectropolarimetry have proven to be very difficult.Aims: Non-thermal radio emission in these objects would most likely be due to synchrotron radiation. As a magnetic field is required for the production of synchrotron radiation, this would be strong evidence for the presence of a magnetic field. Such non-thermal emission has already been observed from the strongly magnetic Ap/Bp stars.Methods: We have performed 6 and 21 cm observations using the WSRT and use these, in combination with archival VLA data at 3.6 cm and results from the literature, to study the radio emission of 5 selected candidate magnetic O stars.Results: Out of our five targets, we have detected three: ? Per, which shows a non-thermal radio spectrum, and a Cam and ? Cep, which show no evidence of a non-thermal spectrum. In general we find that the observed free-free (thermal) flux of the stellar wind is lower than expected. This is in agreement with recent findings that the mass-loss rates from O stars as derived from the Ha line are overestimated because of clumping in the inner part of the stellar wind.